Pengertian, Tujuan dan Pengembangan Kemampuan Literasi Matematika - Titik Jumrotun Alviyah; Sri Wulandari Danoebroto (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
Mathematical literacy is a basic literation skill that is important for students. The ability of Indonesian students on mathematical literacy is still far behind compared to other countries. Efforts are needed to improve learning in developing students' mathematical literacy skills to be even better. This article aims to examine the main literature sources on mathematical literacy and describe alternative conceptual foundations for developing mathematical literacy that can be further improved and applied in schools. This article presents the understanding of mathematical literacy from several points of view, the objectives of mathematical literacy and its development concept referring to the main and supporting literature sources. Interpretation of several concepts in the literature was done by understanding the perspective on mathematics and describing it narratively. Recommendations and conclusions on the development of mathematical literacy skills that can be further developed in learning planning is presented at the end of the article.